2012
DOI: 10.3109/10428194.2012.663915
|View full text |Cite
|
Sign up to set email alerts
|

Clofarabine, cyclophosphamide and etoposide for the treatment of relapsed or resistant acute leukemia in pediatric patients

Abstract: Clofarabine is a promising new chemotherapeutic agent that is active in the treatment of pediatric acute leukemia. Forty children (16 with acute myeloid leukemia [AML], 24 with acute lymphoblastic leukemia [ALL]), aged 1-20 years (median 7.6 years) with relapsed or refractory ALL or AML were treated because of resistance to first-line treatment (n =5), or for first (n =22), second (n =11) or third relapse (n =2). They received clofarabine (40 mg/m(2)/day) associated with etoposide (100 mg/m(2)/day) and cycloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…Clofarabine is typically administered in combination with cyclophosphamide and etoposide, and this combination shows a synergistic effect in relapsed/refractory pediatric ALL patients . Therefore, we next assessed whether this CLO/ETO/CTX combination could be used in PDX models to better facilitate drug selection for patients.…”
Section: Resultsmentioning
confidence: 99%
“…Clofarabine is typically administered in combination with cyclophosphamide and etoposide, and this combination shows a synergistic effect in relapsed/refractory pediatric ALL patients . Therefore, we next assessed whether this CLO/ETO/CTX combination could be used in PDX models to better facilitate drug selection for patients.…”
Section: Resultsmentioning
confidence: 99%
“…The resistance of tumor cells to anticancer agents continues to be a problem that hinders successful chemotherapy. How to increase chemosensitivity in relapsed leukemia has become an important research objective [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…108 In subsequent, small phase II studies in pediatric patients (age 1-21 years) with relapsed/refractory ALL, this combination induced response rates (CR plus CRp) of 42% to 44%. 109,110 A multicenter retrospective study of data from pediatric patients treated with clofarabine outside of the clinical trial setting (n = 23; age 0-17 years) reported that among those treated with the combination of clofarabine, cyclophosphamide, and etoposide (n = 18), the CR rate was 56%. 111 The combination regimen of clofarabine, cyclophosphamide, and etoposide has been associated with prolonged and severe myelosuppression, febrile episodes or severe infections (including sepsis or septic shock), mucositis, and liver toxicities including fatal venoocclusive disease (the latter occurring in the postallogeneic HCT setting).…”
Section: Treatment Of Relapsed Ph-negative Allmentioning
confidence: 99%
“…111 The combination regimen of clofarabine, cyclophosphamide, and etoposide has been associated with prolonged and severe myelosuppression, febrile episodes or severe infections (including sepsis or septic shock), mucositis, and liver toxicities including fatal venoocclusive disease (the latter occurring in the postallogeneic HCT setting). [109][110][111] Moreover, data are very limited with this combination regimen in adult patients with ALL. Because the use of this regimen requires close monitoring and intensive supportive care measures, patients should only be treated in centers with expertise in the management of ALL.…”
Section: Treatment Of Relapsed Ph-negative Allmentioning
confidence: 99%